TH E SHOCK WAVE HEATING MECHANISM OF PULSATING STAR CHROMOSPHERES - Andrievsky, S. M. (Одеські астрономічні публікації, 2017)
A mechanism is suggested which explains the origin and variability of chromospheric emission in the centres of the Mgll h and k lines in the spectra of pulsating stars. According to the model the emission originates from gas heated by a shock wave passing though the outer layers of tie star’s atmosphere.